Soluble transferrin receptor in sickle cell diseases: correlation with spleen function - Grotto, Helena Zerlotti Wolf; Kimura, Elza Miyuki; Carneiro, Márcia Victor (São Paulo Medical Journal, 1999)
OBJECTIVE: To correlate spleen function with soluble transferrin receptor (sTfR) levels and red cell ferritin (RCF) values in patients with sickle cell diseases. DESIGN: Prospective study. LOCATION: University Hospital, School of Medical Sciences, State University of Campinas; a tertiary hospital. PARTICIPANTS: 60 patients with sickle cell diseases, in a steady state, who had not received blood transfusions for 3 months; 28 normal individuals with no clinical or laboratory signs of anemia. MEASUREMENTS: Determination of serum iron, transferrin iron-binding capacity, serum ferritin, RCF and sTfR. Evaluation of spleen function: erythrocytes with pits were quantified. RESULTS: Patients with sickle cell anemia had sTfR levels significantly higher than in normal individuals or those with HbSC (p=0.0001) and there was an inverse correlation between sTfR and fetal Hb (p=0.0016). RCF values were significantly higher in sickle cell anemia patients than in normal individuals or those with HbSC (p=0.0001), and there was a correlation between RCF and pitted erythrocytes (p=0.0512). CONCLUSION: The association between sTfR and fetal Hb confirms the contribution of fetal Hb to improving the hemolytic state by minimizing the consequent reactive erythrocyte expansion. High sTfR levels are not related to the degree of spleen function deficiency seen in sickle cell disease patients. The deficiency in the exocytosis process of the spleen occurring in sickle cell anemia patients may contribute to their accumulation of RCF.